Stigma reduction and provision of mental health services in the public health response to COVID-19 - M, Shreyaswi Sathyanath; Sathyanath, Shashwath (Indian Journal of Community Health, 2020)
Stigma reduction and provision of mental health services are unique challenges associated with the new COVID 19 pandemic. Stigma and discrimination may affect the patients diagnosed with COVID 19, those who have been placed under quarantine as well as the frontline. Effective, accurate and timely communication delivered in a coordinated manner along with community engagement is the cornerstone for stigma reduction and promotion of mental health. Although several steps have been taken to address stigma and promote mental health, it is imperative that a clearly defined strategy be put in place to integrate mental health services into the public health response to COVID 19.